Peningkatan Pemahaman Matakuliah Jaringan Komputer Dasar Menggunakan Simulator Jaringan Cisco Packet Tracer - Martanto .; Saeful Anwar (Jurnal ICT : Information Communication & Technology, 2020)
Students who study at STMIK IKMI Cirebon have diverse school backgrounds, so not all students have an adequate base of computer science, this can be seen in the final examination results of the basic computer network subject for the previous generation of Informatics Management study program, the KHS score got better because it is helped by the value of the assignment and the value of the certification. Quasiexperiments is a method used in this study by using Time Series Design as a collaboration in classroom action research. The results of this study get the Asymp value. Sig. for the ANOVA test of 0,000. The ANOVA value of 0.000 indicates that the PreTest and PostTest scores have a difference where the PostTest results have been proven to be better, so it can be concluded that learning activities using the Cisco Packet Tracer Network Simulator [1] can improve student understanding